SUSCEPTIBILITY OF LANDSLIDE IN THE FOREST REGION OF THE CIMANUK RIVER CATCHMENT AREA, WEST JAVA, INDONESIA - -, Dicky Muslim (Bulletin of Scientific Contribution, 2009)
In Indonesia, a program in rehabilitation of forest region on destructed land had become a national movement (GNRHL) by the central government on the river catchment area since 1999. Destructed forest implies to the decreasing its natural function which physically related with geological hazards such as erosion, landslide, etc. In the forest region of the Cimanuk River catchment area, landslide frequently occurs every year. As an initial step to build the early warning system, mapping of landslide susceptibilityis necessary. In this study, landslide susceptibility is approached through analysis of Geological map, rock/soil engineering formation, quantitative analysis of slope stability (SF) and plotting of previous reported landslides in the forest region.Result of analyses shows that there are 4 types of susceptibility on the study area. Highly susceptible is characterized by mountainous to hilly area on thick soil of fine grain sedimentary rocks with high density lineations representing geological structures. Medium susceptibility is characterized by hilly area on thick to thin soil of coarse grain rocks with medium density lineations. Low susceptibility is characterized by hilly area on thin soil of coarser grain from sedimentary and volcanic rocks. Very low susceptibility area is characterized by soil on alluvial plain. Special attention is carried out on swelling-shrinking type of soils, neotectonism and bare forest area on the toe of slope.